Study on mechanical properties and microscopic damage mechanism of tight sandstone reservoir under uniaxial compression - Huang, Jin; Xing, Jiacheng; Liao, Xingchuan; Ren, Yixing; Ding, Keer; Tan, Jin (Frontiers in Energy Research, 2023)
Due to the characteristics of low porosity, low permeability and serious anisotropy in tight reservoirs, it is difficult for conventional hydraulic fracturing theory to accurately guide the efficient exploitation of tight reservoirs. It has been shown that the reservoir rock mechanical properties are the key factor impacting the fracturing effect, but the current research on the damage properties of tight reservoir rocks is not comprehensive enough. Therefore, in order to improve the fracturing theory of tight reservoirs, this paper first explores the evolution mechanism of rock fractures through uniaxial compression experiments. Secondly, based on the particle discrete element method, the damage and failure process of tight sandstone under uniaxial compression is simulated from the microscopic scale. The test results show that the rock failure mainly includes tensile failure, shear failure, and tensile-shear failure; Internal micro-fractures will interconnect during rock destruction to form primary fractures through the rock mass, while secondary micro-fractures will also be generated. The numerical simulation results show that when the rock is subjected to tensile-shear failure, with the increase of load, tensile micro-fractures are mainly produced in the specimen, accompanied by a few shear fractures. Under the joint action of shear failure and tensile failure, V-shaped cracks are easily formed in rock. The tensile strength of rock is mainly affected by the microscopic tensile strength, and the cohesive force, modulus, stiffness ratio, friction coefficient and friction angle have significant effects on the compressive strength of rock. Therefore, a reasonable choice of microscopic parameters can realistically simulate the compression-tensile strength ratio of the rock. The research results of this paper can provide the theoretical basis of rock mechanics for the efficient exploitation of tight reservoirs.